2014
DOI: 10.1186/1476-069x-13-27
|View full text |Cite
|
Sign up to set email alerts
|

Reducing our environmental footprint and improving our health: greenhouse gas emission and land use of usual diet and mortality in EPIC-NL: a prospective cohort study

Abstract: BackgroundFood choices influence health status, but also have a great impact on the environment. The production of animal-derived foods has a high environmental burden, whereas the burden of refined carbohydrates, vegetables and fruit is low. The aim of this study was to investigate the associations of greenhouse gas emission (GHGE) and land use of usual diet with mortality risk, and to estimate the effect of a modelled meat substitution scenario on health and the environment.MethodsThe usual diet of 40011 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
85
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 25 publications
11
85
2
Order By: Relevance
“…For example, dietary scenarios that primarily aim to lower dietary GHG emissions do not always result in improvements in nutritional quality or health outcomes (Payne et al 2016). In addition, no direct association was observed between diet-related GHG emissions and mortality risk in a previous study (Biesbroek et al 2014). However, adhering to a vegetarian or Mediterranean-style dietary pattern has been shown to be associated with lower environmental impacts and better health (Aleksandrowicz et al 2016;Hallström et al 2015;Nelson et al 2016).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…For example, dietary scenarios that primarily aim to lower dietary GHG emissions do not always result in improvements in nutritional quality or health outcomes (Payne et al 2016). In addition, no direct association was observed between diet-related GHG emissions and mortality risk in a previous study (Biesbroek et al 2014). However, adhering to a vegetarian or Mediterranean-style dietary pattern has been shown to be associated with lower environmental impacts and better health (Aleksandrowicz et al 2016;Hallström et al 2015;Nelson et al 2016).…”
Section: Introductionmentioning
confidence: 81%
“…To exclude dietary over and under reporters, participants in the highest and lowest 0.5% of the ratio of reported energy intake to basal metabolic rate were also excluded (n = 400). Participants with a self-reported history of cancer (n = 1645), diabetes (n = 793), myocardial infarction (n = 531), or stroke (n = 463) at baseline were excluded to include the same population as our previous publications (Biesbroek et al 2014;Biesbroek et al 2017). After these exclusions, 36,209 participants remained for analysis.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…We screened the title and abstracts of 2027 entries from four databases (FCRN Research Library, PubMed, Web of Science and Scopus) and three reference lists. From these, we identified sixteen studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) that present data linking GHGE and nutritional information or health outcomes of 100 dietary patterns and yielding data on 346 cases of effects on nutritional quality or health outcomes of reduced-GHGE diets. Table 2 details the studies included in the current review.…”
Section: Methodsmentioning
confidence: 99%
“…Association between greenhouse gas emissions of diets and health outcomes Five studies reported the GHGE and health outcomes of diets (18,20,21,24,28) . Of these, two were based on reduced meat and/or dairy consumption and found consistent association between reduced GHGE and positive Are the GHGE data used relevant to the review question(s)?…”
Section: Strength Of Associations Between Greenhouse Gas Emissions Ofmentioning
confidence: 99%